Analysis of Customer Experience and Customer Satisfaction on Repurchase Intention with Customer Loyalty as a Mediation Variable at Cafe Dokobox Mamuju - Wardani, Rezki; Wiyadi , Wiyadi; Soepatini, Soepatini; Nasir, M. (International Journal of Management Science and Information Technology, 2024)
This article discusses customer experience and customer satisfaction regarding repurchase interest at Cafe Dokobox Mamuju, with customer loyalty as a mediating variable. This research used a questionnaire to collect data from 200 customers and analyzed using SmartPLS 3. The results show that customer experience and customer satisfaction have a significant influence on loyalty, customer experience also influences repurchase intention. However, customer loyalty does not mediate the influence of customer experience and satisfaction on repurchase intention.